Carbon molecular sieve membrane with atomic aluminum distributed within it

By uniformly distributing aluminum atoms in the carbon molecular filter membrane, a membrane with smaller pore size and uniform pore size distribution was prepared, which solved the problem of insufficient permeability and selectivity in the hydrogen separation and purification process in the prior art, and achieved efficient, stable and economical hydrogen separation effect.

JP2025507358APending Publication Date: 2025-03-18FUNDACION TECNALIA RESEARCH & INNOVATION +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024547438
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2023-02-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient hydrogen permeability and selectivity during hydrogen separation and purification, and there are problems of stability and cost.

Method used

By uniformly distributing aluminum atoms into the carbon molecular filter membrane, using phenol formaldehyde resin and aluminum ions as precursor materials, and after impregnation, drying and carbonization, a carbon molecular filter membrane with smaller pore size and uniform pore size distribution was prepared.

Benefits of technology

The hydrogen permeability and selectivity of the membrane is significantly improved, the chemical stability of the membrane is enhanced, the production cost is reduced, and it can operate at room temperature or at lower temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507358000006
    Figure 2025507358000006
  • Figure 2025507358000007
    Figure 2025507358000007
  • Figure 2025507358000008
    Figure 2025507358000008
Patent Text Reader

Abstract

A supported carbon molecular sieve membrane, in which aluminum is atomically distributed therein, is present in an amount of 15% by weight or less of the carbon molecular sieve membrane; the membrane comprises a pore size distribution in which at least 70% of the pores have a pore size of 0.25 to 0.7 nm; and the supported carbon molecular sieve membrane can be obtained by dip-coating the support with a solution containing phenolic resin and aluminum ions, followed by carbonization, as well as a process for preparing the same. The carbon molecular sieve membrane has a carbon content of 75% to 95% by weight, an oxygen content of 2.5% to 8% by weight, and a hydrogen content of 1.5% to 6% by weight; these CMSM areas are useful for gas separation, H2 recovery from natural gas grids, H2 production from biomass, solvent dehydration, obtaining oxygen-enriched air, or dehydrogenating methylcyclohexane, and are useful as or as part of a catalytic membrane reactor.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of European patent application EP22382118, filed February 14, 2022.

[0002] The present invention relates to carbon molecular sieve membranes (CMSMs) having atomic aluminum incorporated therein and their use in gas separation, for solvent dehydration or as membrane reactors. [Background technology]

[0003] Hydrogen is used as a feedstock in various industrial applications such as refining, ammonia synthesis, and methanol production, and more recently as an energy carrier in the transportation sector for power generation and heating solutions. As a result of the increase in atmospheric CO2, hydrogen is considered a sustainable energy carrier that can enable the much needed transition from fossil to renewable energy sources, a key part of reaching net-zero emissions by 2050. Its high energy density, plus the abundance of the resource, and the zero-carbon emission reactions to generate energy, are considered advantages of hydrogen compared to fossil fuels.

[0004] Hydrogen (H2) can be produced by water hydrolysis, coal gasification, and steam reforming from natural gas, although the latter remains the predominant route.

[0005] The separation and purification of hydrogen from production processes or industrial waste streams remains one of the major challenges in the field. Known techniques for hydrogen purification include pressure swing adsorption, cryogenic distillation, and membrane separation. Membrane separation is a scalable, low-energy-demanding technology that can produce high-purity hydrogen, but the membranes must exhibit high hydrogen permeability and selectivity, long-term stability under separation conditions, and low cost to compete with conventional purification techniques.

[0006] Among membranes for hydrogen separation, palladium (Pd)-based membranes exhibit the highest hydrogen permeance and selectivity due to their inherent mechanism of hydrogen permeation. Unfortunately, Pd is a precious metal and its stability decreases at low temperatures due to hydrogen embrittlement, which can destroy the membrane. As a result, permeation must be carried out at temperatures above 300°C, typically around 400°C. Furthermore, Pd membranes can be poisoned by H2S gas present in the process stream as an impurity.

[0007] Microporous membranes (zeolite, silica, and carbon molecular sieves) are used to separate hydrogen based on size exclusion. However, defect-free zeolite membranes are difficult to prepare, and silica membranes are not stable at high temperatures in the presence of water.

[0008] Carbon molecular sieving membranes (CMSM) are one of the promising alternatives for purifying hydrogen on an industrial scale. CMSM are the product of the thermal decomposition of thermosetting polymers in a non-oxidizing atmosphere. The resulting amorphous carbon structure contains micro- and ultra-micropores that are involved in the separation of gases by molecular sieving (size separation) and adsorption-diffusion (by the interaction of gas molecules with the pore walls). They are fabricated from low-cost materials and are capable of separating gases at room temperature. For mixtures where H2 is present at low concentrations (<10%) and operating at high pressures, CMSM can surpass the permeation performance of Pd membranes.

[0009] The polymer precursors used in the preparation of CMSMs, the carbonization procedure as well as their composition are known to affect the membrane properties and thereby its permeation performance. Thus, for example, MALlosa et al. disclosed the preparation of supported composite alumina-CMSMs (Al-CMSMs), prepared from novolac phenolic resin and boehmite (γ-AlO(OH) nanosheets, improving their hydrophilicity. The authors reported that the pore size and pore size distribution of the pores could be tuned by changing the carbonization temperature of the membranes, and the hydrophilicity could be tuned by the addition of boehmite (see Non-Patent Document 1; and Non-Patent Document 2). The pore sizes disclosed for CMSMs in these publications were around 0.3-0.8 nm.

[0010] It is also known that the pore size and hydrophilicity can be adjusted to optimize water permeation. Thus, US Pat. No. 5,399,433 discloses steam pretreated Al-CMSM and its use in gas separation processes, solvent dehydration, and as a membrane reactor.

[0011] Furthermore, the addition of metals to CMSM has been disclosed for various purposes. Thus, for example, US Pat. No. 5,399,633 discloses a method for ageing-resistant carbon molecular sieve hollow fiber membranes with improved selectivity using metallopolyimides as precursors. The method is based on first immobilizing metal cations in the polyimide hollow fiber membranes by interaction of the metal with the electronegative regions of the polyimide backbone. The metal cations used are transition metals. In this way, the spacing between adjacent carbon chains and / or sheets remains at about the same value, avoiding the tendency to reduce the spacing between adjacent carbon chains and / or sheets in freshly produced metal-CMS membranes without sandwiching cations. This document therefore seeks physical separation to avoid the inherent collapse of the carbon chains (layers).

[0012] US Patent No. 5,399,633 discloses carbon molecular sieve membranes (hollow fibers or thin films) for separating olefins from their corresponding paraffins containing group 13 metals, especially aluminum. The membranes are made by pyrolyzing a precursor polymer (polyimide) with the group 13 metal incorporated therein, the metal being in the reduced state (covalently bonded to carbon or nitrogen or in the metallic state).

[0013] On the other hand, the separation of hydrogen present in mixtures of gases is of great interest for the projected hydrogen economy and due to the growing interest in hydrogen as an energy carrier. The development of CMSM reactors, i.e. devices for simultaneous reactions (steam reforming, dry reforming, autothermal reforming, methanol synthesis, etc.) and membrane-based separations in the same physical device, is also of great interest. These membrane reactors make it possible to improve processes, catalysts and adsorbents, for example, to increase the production efficiency of fuels and petrochemicals, which are highly dependent on separation processes. One continuous extraction of the products can shift the equilibrium and increase the yield and selectivity compared to conventional systems. Moreover, high concentrations of anhydrous solvents are of utmost importance in the chemical industry. In this context, hydrophilic carbon molecular sieve membranes are also particularly good candidates for developing efficient dehydration processes.

[0014] Thus, from what is known in the state of the art, there remains a need to provide CMSMs with increased selectivity and permeation properties for efficient purification of hydrogen from gaseous mixtures and for better efficiency when used as membrane reactors or for solvent dehydration. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] International Publication No. 2021 / 116319 [Patent Document 2] U.S. Patent No. 10112149 [Patent Document 3] International Publication No. 2019 / 089087

Non-licensed literature

[0016] [Non-licensed document 1] MALlosa et al., "Composite-alumina-carbon molecular sieve membranes prepared from Novolac resin and boehmite.Part I: Preparation, characterization and gas permeation studies", Int.J.Hydrogen Energy.2015, vol.40, pp.5653-5663

Non-licensed Document 2

Non-licensed Document 4

[0017] The present inventors have developed supported carbon molecular sieve membranes (CMSMs) by immersing a porous support in an immersion solution containing a mixture of phenol formaldehyde resin and aluminum ions in the form of salt or complex additives as carbon and aluminum precursors, respectively, followed by drying and carbonization to obtain a CMSM with uniform distribution of aluminum in atomic state. The present inventors have found that the incorporation of aluminum in atomic state into CMSM results in supported carbon molecular sieve membranes with pore diameters in the microporous region smaller (<2 nm) than those of known CMSMs prepared from phenol formaldehyde resins, with or without the addition of boehmite. Boehmite is a polymer of hydroxyaluminum. Nanoparticles of boehmite have a size of around 10 nm. By being able to incorporate aluminum in atomic state using phenol resins, the present inventors have achieved not only smaller pore diameters, but also a uniform narrow pore size distribution throughout the membrane, and a stable porous structure.

[0018] Advantageously, the incorporation of atomic aluminum into the CMSM greatly increases the hydrophilicity of the membrane. Moreover, the CMSM has permeation properties well above the Robeson upper limit. Furthermore, because of the single selective layer, additional layers to increase selectivity can be present but are not necessary.

[0019] Thus, the CMSMs of the present invention exhibit an attractive combination of high permeability due to high porosity, selectivity, and chemical stability at high pressure and temperature, even in long-term performance, making these CMSMs particularly useful for industrial gas separations such as hydrogen separation. Moreover, permeation can be carried out at ambient temperature or at lower temperatures down to around -50°C. Moreover, they are prepared from very inexpensive precursors.

[0020] Thus, a first aspect of the present invention relates to a supported carbon molecular sieve membrane having aluminum atomically distributed therein, meaning that aluminum is incorporated in the carbon molecular sieve membrane in the form of a single atom, wherein aluminum is present in an amount of 15% by weight or less of the carbon molecular sieve membrane; the membrane comprises a pore size distribution in which at least 70% of the pores have a pore size of 0.25 to 0.7 nm as measured by perm porosimetry; the carbon content is 75% to 95% by weight, the oxygen content is 2.5% to 8% by weight, and the hydrogen content is 1.5% to 6% by weight; and can be obtained by dip-coating the support with a solution comprising a phenol formaldehyde resin and aluminum ions in the form of a suitable salt or complex as a metal precursor, followed by carbonization, the suitable salt or complex having an organic anion or an organic neutral ligand.

[0021] The Al content is determined by microwave plasma atomic emission spectroscopy (MP-AES) (see the Examples section). The average pore size and pore size distribution are measured by perm porosimetry (see the Examples section for the measurement methodology). Other methods that can be used include CO2 adsorption (see the Pore Size Characterization section in MALlosa et al., “Composite-alumina-carbon molecular sieve membranes prepared from Novolac resin and boehmite. Part II: Effect of the carbonization temperature on the gas permeation properties”, Int. J. Hydrogen Energy. 2015, Vol. 40, pp. 3485-3496).

[0022] A second aspect of the present invention relates to a process for preparing a supported carbon molecular sieve membrane as defined above, comprising: a) providing a porous support; b) providing a coating solution comprising phenol formaldehyde resin as a carbon precursor, a non-aqueous solvent, formaldehyde, an acid acting as a catalyst, and aluminum ions in the form of a suitable salt or complex as a metal precursor; c) immersing a porous alumina support at least once in the solution of step b); d) optionally drying the coated support-loaded aluminum of step c); e) heating the dried support of step d) to a final pyrolysis temperature and non-oxidizing atmosphere sufficient to form a supported carbon sieve membrane containing aluminum atomically distributed therein; f) cooling the supported carbon sieve membrane of step e) to room temperature, wherein the suitable salt or complex has an organic anion or organic neutral ligand.

[0023] A third aspect of the present invention relates to a process for separating a gas molecule, H2, from a gas mixture of the gas molecule and at least one other gas molecule, comprising: a) providing a supported carbon molecular sieve membrane as defined above; b) providing a gas mixture comprising at least two gases; and c) feeding the gas mixture to the supported carbon molecular sieve membrane at a temperature of -80°C to 300°C to obtain a retentate stream having a reduced concentration of the gas molecule and a permeate stream having an increased concentration of the gas molecule.

[0024] A fourth aspect of the present invention relates to the use of a supported CMSM as defined above for solvent dehydration.

[0025] A final aspect of the present invention relates to the use of a supported CMSM as defined above as a catalytic membrane reactor or as part of a catalytic membrane reactor. [Brief description of the drawings]

[0026] [Figure 1A] FIG. 1 shows a schematic diagram of the gas permeation setup. [Figure 1B] FIG. 1 is a schematic diagram of a perm porosimeter designed to measure the pore size of a tubular CMSM using water and N2 as the adsorbent and inert gas. [Diagram 2] Cross-sectional SEM images of CMSM M0 (a) and M0.7 (b) are shown. [Diagram 3] The effect of Al(acac)3 concentration in the immersion solution on the viscosity of the solution and the thickness of the CMSM is shown. [Figure 4] 1 shows the XRD spectrum of unsupported CMSM. [Diagram 5] 4 shows water adsorption as a function of Al wt % content in the film. [Figure 6] Figure 1 shows the pore size distribution measured by perm porosimetry of unsupported CMSM with various Al(acac)3 contents in the immersion solution. [Figure 7] 13 shows N2 permeance versus applied pressure for the CMSM at 45° C. [Figure 8]The effect of operating temperature on the H2 / N2 ideal selectivity of CMSM at 6 bar ΔP is shown. [Figure 9] A comparison of the CMSM thus prepared with polymer membranes according to Robeson's upper limit is presented. [Figure 10] 1 shows long-term permeation H2 and H2 / N2 tests of M4 CMSM at 150° C. and 6 bar ΔP. [Figure 11] SEM-EDX analysis of Al, C and O is shown. [Figure 12] Figure 1 shows the N2 permeance as a function of permeation temperature for CMSM with various Al(acac)3 contents. ΔP 6 bar [Figure 13] Figure 1 shows the H2 permeance as a function of permeation temperature for CMSM with various Al(acac)3 contents. ΔP 6 bar [Figure 14] Figure 1 shows the N2 permeability as a function of permeation temperature for CMSM with various Al(acac)3 contents. ΔP 6 bar [Figure 15] Figure 1 shows the H2 permeability as a function of permeation temperature for CMSM with various Al(acac)3 contents. ΔP 6 bar Detailed Description of the Invention

[0027] All terms used herein in this application are to be understood in their ordinary sense as known in the art unless otherwise specified. Definitions of other more specific terms used in this application are as follows and are intended to be applied uniformly throughout the specification and claims unless a definition expressly set forth provides a broader definition.

[0028] The terms "phenol formaldehyde resin" and "phenolic resin" are used synonymously herein.

[0029] The term "pore size" as used herein refers to the average pore diameter and is measured by perm porosimetry. This technique measures the average active pore size of the CMSM.

[0030] As used herein, the term "aluminum atomic-carbon molecular sieve membrane" or "Ala-CMSM" refers to a carbon membrane having aluminum in atomic form dispersed in a carbon matrix.

[0031] The expression "aluminum atomically distributed in the CMSM" means that aluminum is incorporated in the CMSM in the form of a single atom, which can form a complex with the OH groups of the phenolic resin, which behaves as a metal chelating crosslinker.

[0032] The term "permeate flow" is defined as the volume of gas passing through a membrane per unit time. This value is determined experimentally using a flow meter.

[0033] The term "permeate flux" is defined as the volume that flows through a membrane per unit area per unit time. This value is calculated by dividing the "permeate flow" by the area of ​​the membrane.

[0034] The term "permeance" is defined as the volume of feed gas passing through unit area of ​​membrane under unit time and unit pressure gradient, and the common unit used in CMSM is mol m -2 s -1 ·Pa -1 This value is calculated by dividing the "permeate flux" by the pressure difference between the retentate and the permeate.

[0035] The term "permeability" is defined as the transport flux of a material through a membrane per unit driving force per unit membrane thickness.

[0036] The term "permselectivity" or ideal selectivity with respect to gases refers to the ratio of the permeances of two single gases at the same temperature.

[0037] The term "pressure differential" refers to the difference between the gas pressure in the retentate and the gas pressure in the permeate.

[0038] The term "partial pressure differential" for a given gas refers to the difference between the partial pressure of the gas in the retentate and the partial pressure of the gas in the permeate.

[0039] The term "room temperature" refers to a temperature of about 20°C to about 25°C.

[0040] As used herein, the term "atmospheric pressure" is intended to refer to atmospheric pressure substantially equal to 101.3 kPa (ie, 760 mmHg) ± 15 kPa.

[0041] The terms "pyrolysis" and "carbonization" are used interchangeably herein.

[0042] The supported carbon molecular sieve membrane of the present invention comprises a support and a carbon molecular sieve membrane, which may also be referred to as a carbon selective layer.

[0043] Please note that as used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0044] As described above, a supported carbon molecular sieve membrane having aluminum atomically distributed therein, the aluminum being present in an amount of 15% by weight or less of the carbon molecular sieve membrane; the membrane comprising a pore size distribution in which at least 70% of the pores have a pore size between 0.25 and 0.7 nm; can be obtained by dip-coating the support with a solution comprising a phenolic resin and aluminum ions, followed by carbonization. The pore size distribution is measured using perm porosimetry.

[0045] Suitable aluminum salts are those that are soluble in the organic solvent used in the immersion solution. Other anions that can be destroyed during carbonization can also be used. In certain embodiments, the anion of the aluminum salt is an organic anion. In certain embodiments, the aluminum salt used is aluminum acetylacetonate. The use of aluminum acetylacetonate is advantageous because it is soluble and stable in organic solvents.

[0046] The use of aluminum in the form of a complex is also advantageous due to its stability, helping it remain as a single atom until the ligand exchanges with the OH group of the phenolic resin. The ligand in the complex can be an organic anion or an organic neutral ligand. Examples of organic neutral ligands are amines such as ethylenediamine or diethyltriamine. Further examples of aluminum complexes are 8-hydroxyquinoline complexes; alizarin complexes; salophen complexes; acetic acid, (ethylenedinitrilo)tetra-, aluminum(III) complexes; and mixed ligand complexes of Al(III) with o-nitrophenol, 1-nitroso-2-naphthol, 2,4-dinitrophenol, 8-hydroxyquinoline, 2,4,6-trinitrophenol, or o-nitrobenzoic acid, and ethylenediamine.

[0047] In a particular embodiment, the supported carbon molecular sieve membrane (Ala-CMSM) of the present invention has aluminum present in an amount of 0.1% to 11% by weight of the carbon molecular sieve membrane. In another particular embodiment, the supported carbon molecular sieve membrane of the present invention has aluminum present in an amount of 1% to 11% by weight of the carbon molecular sieve membrane. In another particular embodiment, the supported carbon molecular sieve membrane of the present invention has aluminum present in an amount of 3% to 10.5% by weight of the carbon molecular sieve membrane. In a particular embodiment, the supported carbon molecular sieve membrane of the present invention has aluminum present in an amount of 4% to 9% by weight of the carbon molecular sieve membrane. In another particular embodiment, the supported carbon molecular sieve membrane of the present invention has aluminum present in an amount of 8% to 9% by weight of the carbon molecular sieve membrane. In another particular embodiment, the supported carbon molecular sieve membrane of the present invention has aluminum present in an amount of 1% to 9% by weight of the carbon molecular sieve membrane.

[0048] In another specific embodiment, the supported carbon molecular sieve membrane of the present invention has a carbon content of 75 to 95% by weight, an oxygen content of 2.5 to 8% by weight, and a hydrogen content of 1.5 to 6% by weight. The C, H, and O contents are determined using a Thermo Scientific Flash smart-CHNS / O analyzer.

[0049] SEM-EDX analysis of the CMSM membrane according to the invention confirms that Al, C, and O are well distributed in the membrane. It is believed that Al(III) forms a complex with the OH groups of the phenolic resin, which behaves as a metal chelating crosslinker. The formation of the complex, together with the increase in the viscosity of the immersion solution used to prepare the membrane due to the formation of the complex, hinders the migration of Al(III) and avoids the formation of polyaluminum compounds such as alumina (Al2O3) and boehmite (γ-AlO(OH). This is confirmed by the XRD spectrum of a sample of the CMSM according to the invention, where no peaks of γ-Al2O3 / boehmite (γ-AlO(OH) are observed.

[0050] In certain embodiments, optionally in combination with the above or below embodiments or particle size distribution, the pore size distribution is such that at least 70% of the pores are 0.7 nm or less, preferably between 0.25 and 0.7 nm.In another particular embodiment, the pore size distribution is such that at least 75% of the pores are 0.7 nm or less, i.e. have a pore size of 0.7 nm or less, preferably between 0.25 and 0.7 nm.In another particular embodiment, the pore size distribution is such that at least 80% of the pores are 0.7 nm or less, preferably between 0.25 and 0.7 nm.In another particular embodiment, the pore size distribution is such that at least 85% of the pores are 0.7 nm or less, preferably between 0.25 and 0.7 nm.In another particular embodiment, the pore size distribution is such that at least 90% of the pores are 0.7 nm or less, preferably between 0.25 and 0.7 nm. In another particular embodiment, the pore size distribution is such that at least 95% of the pores are 0.7 nm or less, preferably between 0.25 and 0.7 nm. In another particular embodiment, the pore size distribution is such that 100% of the pores are 0.7 nm or less, preferably between 0.25 and 0.7 nm. All percentages used to express the above pore size distribution are expressed as percentages of the number of pores.

[0051] In another particular embodiment, optionally in combination with the above and / or below embodiment of particle size distribution, the pore size distribution is such that at least 60% of the pores are 0.6 nm or less, i.e. 0.6 nm or less, preferably between 0.25 and 0.6 nm.In another particular embodiment, the pore size distribution is such that at least 65% of the pores are 0.6 nm or less, preferably between 0.25 and 0.6 nm.In another particular embodiment, the pore size distribution is such that at least 80% of the pores are 0.6 nm or less, preferably between 0.25 and 0.6 nm.In another particular embodiment, the pore size distribution is such that at least 85% of the pores are 0.6 nm or less, preferably between 0.25 and 0.6 nm.In another particular embodiment, the pore size distribution is such that at least 90% of the pores are 0.6 nm or less, preferably between 0.25 and 0.6 nm. In another particular embodiment, the pore size distribution is such that at least 95% of the pores are 0.6 nm or less, preferably between 0.25 and 0.6 nm. In another particular embodiment, the pore size distribution is such that 100% of the pores are 0.6 nm or less, preferably between 0.25 and 0.6 nm. All percentages used to express the pore size distribution above are expressed as percentages of the number of pores.

[0052] In another particular embodiment, optionally in combination with any of the above embodiments of particle size distribution, the pore size distribution is such that at least 40% of the pores are 0.5 nm or less, i.e., have a pore size less than 0.5 nm, preferably between 0.25 and 0.5 nm. In another particular embodiment, the pore size distribution is such that at least 45% of the pores are 0.5 nm or less. In another particular embodiment, the pore size distribution is such that at least 50% of the pores are 0.5 nm or less, and the pore size distribution is such that at least 55% of the pores are 0.5 nm or less. In another particular embodiment, the pore size distribution is such that at least 60% of the pores are 0.5 nm or less. In another particular embodiment, the pore size distribution is such that at least 65% of the pores are 0.5 nm or less. All percentages to express the above pore size distribution are expressed as percentages of the number of pores.

[0053] In another particular embodiment, the pore size distribution is such that at least 70% of the pores are 0.7 nm or less and at least 40% of the pores are 0.5 nm or less. In another particular embodiment, the pore size distribution is such that at least 90% of the pores are 0.7 nm or less and at least 50% of the pores are 0.5 nm or less. In another particular embodiment, the pore size distribution is such that 100% of the pores are 0.7 nm or less and at least 55% of the pores are 0.5 nm or less. In another particular embodiment, the pore size distribution is such that 100% of the pores are 0.7 nm or less and at least 65% of the pores are 0.5 nm or less. The preferred ranges are the ranges mentioned above, with the lower part of the range being 0.25 nm and the higher part of the range being the end point indicated for the above range. All percentages to express the above pore size distribution are expressed as a percentage of the number of pores.

[0054] In a particular embodiment, the supported carbon molecular sieve membrane is one in which the support is a porous ceramic support that is an inorganic non-metallic solid based on an oxide, nitride, boride, or carbide, preferably selected from the group of alpha alumina, titanium oxide, zirconium oxide, ceria, and gamma alumina. In another particular embodiment, the supported carbon molecular sieve membrane is one in which the support is a porous carbon support.

[0055] In another particular embodiment, the supported carbon molecular sieve membrane is one in which the support is a porous alumina support.

[0056] In certain embodiments, the supported carbon molecular sieve membrane has a shape that may be tubular, hollow fiber, or planar.

[0057] In certain embodiments, a supported CMSM of the present invention comprises a single selective layer on the exterior surface of the porous support.

[0058] The thickness of the CMSM of the present invention depends on the pore size of the support directly beneath the carbon layer. As an example, if the porous support has a defect-free pore size of 5 nm, a CMSM of the present invention having a thickness of 20 nm can be prepared.

[0059] The thickness of the CMSM layer depends on the content of aluminum salt or complex (Al(acac)3) in the immersion solution, which also affects the pore size and pore size distribution of the membrane. For example, when the amount of Al(acac)3 in the immersion solution used to prepare CMSM is 0.7 wt%, the thickness of the membrane increases from 1.5 μm in the case of CMSM without aluminum to 2 μm. According to SEM images, a defect-free continuous layer is deposited in the membrane.

[0060] The permeation properties of the membranes versus the Al content in the membrane follow a volcano shape; for example, the membrane prepared by MP-AES with 4 wt% Al(acac)3 soaking solution containing 8.3% Al in the membrane had the best properties and was stable for 720 h with hydrogen at 150 °C and 6 bar pressure difference (20% H2 / 80% N2). All CMSMs have permeation properties well above the Robeson upper limit. In a particular embodiment, the Al content is obtained using 3-5 wt% Al(acac)3 in the soaking solution.

[0061] In another particular embodiment, the supported carbon molecular sieve membrane of the present invention is one in which the membrane has a hydrogen / nitrogen permeation selectivity in the range of 20-350° C. greater than 3.7.

[0062] In another particular embodiment, the supported carbon molecular sieve membranes of the present invention have a hydrogen permeance that exceeds the Robeson upper limit plot of polymer membranes.

[0063] In another particular embodiment, in combination with any of the above or below aspects or embodiments, the supported carbon molecular sieve membrane of the invention is free of silica.

[0064] All specific embodiments disclosed above for the supported carbon molecular sieve membrane, in any combination, are also specific embodiments of the present invention.

[0065] The supported carbon molecular sieve membrane of the present invention can be prepared by dip-coating a porous alumina support in a dip solution. The process includes: a) providing a porous support; b) providing a coating solution containing phenol formaldehyde resin as carbon precursor, a non-aqueous solvent, formaldehyde, acid, and aluminum ions in the form of a suitable salt or complex as metal precursor; c) dipping the porous alumina support at least once in the solution of step b); d) optionally drying the coated aluminum-carrying support of step c); e) heating the dried support of step d) to a final pyrolysis temperature and non-oxidizing atmosphere sufficient to form a supported carbon sieve membrane containing aluminum; f) cooling the supported carbon sieve membrane of step e) to room temperature. Suitable salts or complexes are those with organic anions or organic neutral ligands.

[0066] Optionally, an amine such as ethylenediamine can be added to the soaking solution.

[0067] The supported carbon molecular sieve membrane of the present invention can also be defined by its preparation process.Therefore, the supported carbon molecular sieve membrane obtainable by the above-defined process is part of the present invention.All specific embodiments or combinations of embodiments disclosed above or below, both for the CMSM of the present invention or for the process for their preparation, are also specific embodiments or combinations of embodiments for this aspect of the present invention.

[0068] A particular embodiment of the preparation process is one in which the support is a tubular α-alumina support (α-Al2O3).

[0069] In another particular embodiment, the solvent has a boiling point of 60° C. or higher. In another particular embodiment, the solvent has a boiling point of 100° C. or higher. Examples of suitable solvents are N-methyl 2-pyrrolidone, ethanol, methanol, or chloroform.

[0070] Examples of suitable acids are carboxylic acids such as oxalic acid.

[0071] In a particular embodiment, the aluminum ion in the form of a suitable salt or complex is in the form of a soluble salt in an organic solvent. In another particular embodiment, the aluminum ion in the form of a soluble salt or complex is aluminum acetylacetonate (Al(acac)3).

[0072] In a particular embodiment, the phenol formaldehyde resin used in the present invention is a synthetic resin. The resin may be, for example, a novolac resin. Such a resin is formed between phenol and formaldehyde in an acidic medium. As an example, the formaldehyde / phenol ratio may be 0.75-0.85% by weight. The resin may also be a resole resin derived from the reaction between phenol and formaldehyde in a basic medium. The phenol / formaldehyde ratio in the resole resin is >1% by weight. Other phenolic resins may also be used.

[0073] Further examples of suitable resins are phenol-urea-formaldehyde, phenol-melamine-formaldehyde, dicyclopentadiene-phenol, phenol and formaldehyde derivatives such as resole-formaldehyde, hydroquinone derivatives or polybenzoxazines.

[0074] In another particular embodiment, the process is one in which the phenol formaldehyde resin can be obtained by reacting phenol with formaldehyde in an acidic medium at a temperature of 80 to 110° C. The acidic medium can be provided by an acid such as, for example, oxalic acid.

[0075] Phenolic resins, such as novolac resins, are desirable precursors for preparing CMSMs, since they are inexpensive, have a high carbon yield, and exhibit the advantages of withstanding high temperatures without losing their shape. Phenolic resins are the products of the polycondensation reaction of phenol with formaldehyde; their structure and properties depend on the formaldehyde / phenol ratio (F / P), catalyst, pH and temperature. Novolac resins are obtained in an acidic medium and the amount of formaldehyde usually have an F / P of ca. 0.75-0.85.

[0076] Generally, the amount of novolak in the coating solution is from 5 to 25% by weight, preferably 20% by weight; the amount of N-methyl-2-pyrrolidone is from 70 to 85% by weight, preferably 78% by weight, the amount of formaldehyde is from 0.5 to 5% by weight, preferably 1.6% by weight, and the amount of oxalic acid is from 0.1 to 1% by weight, preferably 0.4% by weight.

[0077] In certain embodiments, the amount of aluminum salt or complex, particularly Al(acac)3, in the immersion solution is 0.5 to 6% by weight. In certain embodiments, the amount is 2 to 5% by weight.

[0078] In a particular embodiment, the aluminum salt is aluminum acetylacetonate (Al(acac)3). In general, the amount of Al(acac)3 is 0.5 to 6 wt. % of the immersion solution. In a particular embodiment, the amount of Al(acac)3 is 2 to 5 wt. %. In another particular embodiment, the amount of Al(acac)3 is 4 wt. %. Supported carbon molecular sieve membranes according to the present invention prepared with 4 wt. % Al(acac)3 in the immersion solution exhibit excellent properties and are stable for 720 hours with hydrogen at 150° C. and 6 bar pressure difference.

[0079] The process of immersing the porous alumina support in the immersion solution is repeated 1 to 10 times. In a particular embodiment, the process is a process in which the immersion step is performed only once. In another particular embodiment, the process is a process in which the immersion step is repeated 2 to 6 times. In another particular embodiment, the process is a process in which the immersion step is repeated 3 to 5 times. In another particular embodiment, the process is a process in which the immersion step is repeated 5 times.

[0080] This treatment is usually carried out at room temperature for a suitable time. A suitable time may be between 5 and 120 seconds. Generally, it is sufficient to maintain the porous alumina support in the immersion solution for between 5 and 120 seconds, in particular around 30 seconds. It is generally carried out under stirring, for example at a speed of 5 mm / s. The immersion coating is generally repeated several times, with an interval that may be, for example, 5 minutes, and generally a time between cycles of around 10 to 40 seconds, in particular around 20 seconds, is sufficient.

[0081] In certain embodiments, the drying step of the coated support is carried out at a temperature below the boiling point of the solvent used in the immersion solution, for example, when N-methyl-2-pyrrolidone is used, the temperature is between 90 and 110°C.

[0082] More particularly, this is carried out under an argon atmosphere.

[0083] In another particular embodiment, the process is one in which the pyrolysis temperature is between 350° C. and 1100° C. In another particular embodiment, the process is one in which the pyrolysis temperature is between 450° C. and 900° C. In another particular embodiment, the process is one in which the pyrolysis temperature is between 500° C. and 700° C. In another particular embodiment, the process is one in which the pyrolysis temperature is 500° C.

[0084] In another particular embodiment, the process is one in which the pyrolysis step e) is carried out under a non-oxidizing atmosphere or under vacuum. In another particular embodiment, the inert atmosphere is selected from the group consisting of an argon atmosphere, a nitrogen atmosphere, a helium atmosphere, an H2 atmosphere, and an NH3 atmosphere. In another particular embodiment, the non-oxidizing atmosphere is an argon atmosphere. The carbonization pressure is in the range of 2 mbar to 6 bar.

[0085] In a particular embodiment, the pyrolysis is carried out in a tubular oven with a heating ramp of 1° C. / min up to 500° C. and then maintained at 500° C. for 3 hours.

[0086] In certain embodiments, the process involves storing the CMSM at 100% relative humidity after carbonization to stabilize the hydrophilic sites within the CMSM. The storage time at such relative humidity can be from a few hours to longer times, such as about a month.

[0087] All specific embodiments disclosed above for the process, in any combination, are also specific embodiments of the present invention.

[0088] The CMSM of the present invention shows very good gas separation ability. The CMSM of the present invention is useful for H2 separation. Thus, a process for separating a gas molecule, which is H2, from a gas mixture of the gas molecule and at least one other gas molecule, comprising: a) providing a supported carbon molecular sieve membrane as defined above; b) providing a gas mixture comprising at least two gases; and c) feeding the gas mixture to the supported carbon molecular sieve membrane at a temperature between -80°C and 300°C to obtain a retentate stream having a reduced concentration of the gas molecule and a permeate stream having an increased concentration of the gas molecule, is also part of the present invention. In a particular embodiment, the temperature at which the gas mixture is fed is between -10°C and 300°C. In another particular embodiment, the temperature at which the gas mixture is fed is between 0°C and 300°C. In another particular embodiment, the temperature at which the gas mixture is fed is between 5°C and 250°C.

[0089] This aspect may also be defined as the use of CMSM as defined above for separating a gas from a gas mixture, which may be used, for example, for hydrogen recovery from waste streams.

[0090] Membrane processes for gas separation are characterized by the fact that the feed stream, which is a gas mixture, is split into two streams: retentate and permeate. The retentate is the part of the feed that does not pass through the membrane, and the permeate is the part of the feed that does pass through the membrane, i.e. the separated gas.

[0091] In certain embodiments, step c) of the third aspect of the invention, i.e., feeding of the gas mixture to the supported carbon molecular sieve membrane, is carried out at a temperature of from 5° C. to 250° C., from 5 to 120° C., from 15° C. to 120° C., from 15° C. to 100° C., from 15° C. to 70° C., or from 20° C. to 50° C., for example at 40° C. In certain embodiments, the feeding is carried out at room temperature.

[0092] In a particular embodiment, the separation process is one in which the gas mixture comprising at least two gases is selected from the group consisting of H2 / CH4; H2 / N2; H2 / CO2. In a particular embodiment, the gas mixture may contain some water, i.e., is non-anhydrous. In another embodiment, the gas mixture is anhydrous.

[0093] In a particular embodiment, the CMSM of the present invention is used for H2 recovery from the natural gas grid. The wide natural gas grid infrastructure can be used to store and distribute H2 present in low concentrations (<20%) blended with natural gas (CH4); then, at the end user, H2 can be separated and the CMSM of the present invention can be used for such separation. In a particular embodiment, the membrane of the present invention is used at 30°C with an inlet pressure of 7.5 bar and a permeate pressure of 0.01 bar.

[0094] Purities of over 99% can be obtained. Advantageously, the membranes of the present invention do not undergo concentration polarization, especially at high pressures and low H2 contents, as occurs with other membranes, such as PdAg membranes. Furthermore, no reduction in hydrogen permeance is shown between pure gas permeation tests and mixture permeation tests. Sensitivity analysis shows that at low concentrations of H2 and high pressures, the use of the membranes of the present invention is more economical than PdAg membranes, with the same recovery and similar purity, even without considering the cost, where the permeation of the PdAg membrane can be carried out at 400°C, whereas the membranes of the present invention can be carried out at 20°C.

[0095] In another specific embodiment, the CMSM of the present invention is used for H2 production from biomass. Dark fermentation (DF) is the most developed method for biohydrogen production. It has several advantages such as low energy demand, high bacterial growth rate, minimal pollution generation, low capital cost, higher hydrogen production rate, as well as no oxygen limitation problem for small-scale production. However, if H2 is not sufficiently removed, it will accumulate in the headspace of the fermentation and inhibit the H2-forming reaction from taking place due to thermodynamic constraints. The use of CMSM of the present invention allows for continuous and effective removal of H2. This process typically produces hydrogen in the range of 35-65% by volume, with by-products of CO2, volatile organic compounds (VOCs), hydrogen sulfide (H2S), and ammonia (NH3).

[0096] The CMSM of the present invention is well suited for this process since it is not poisoned by H2S, does not swell, and has enhanced permeability properties in the presence of moisture in the environment.

[0097] In another particular embodiment, the CMSM of the present invention is used for H2 / CO2 separation. The actual effort is to improve H2 / CO2 separation. Unlike the expensive Pd membrane reactors that produce pure H2 from CH4 at 450-500°C and the polymer membranes that are not stable at high temperatures, the CMSM of the present invention has good H2 selectivity and can operate in the range of 100-300°C.

[0098] The CMSM of the present invention can also be used to enrich oxygen-enriched air, which is highly demanded for various industrial applications such as medical, chemical and enhanced combustion processes membrane technology, and CMSM in particular has great potential to compete with current separation technologies such as PSA and cryogenic distillation.

[0099] The supported CMSM membrane of the present invention may be used in other applications, which also form part of the present invention.

[0100] Thus, one of these applications is the use of the supported CMSM membrane of the present invention for solvent dehydration, i.e., removal of water from organic solvents to obtain organic solvents containing less than 1% water, preferably less than 0.5% water, more preferably less than 0.1% water. Examples of organic solvents include methanol, ethanol, propanol, n-butanol, iso-butanol, tert-butanol, acetone, dimethyl ether, dimethyl carbonate, tetrahydrofuran, acetonitrile, dioxane, acetic acid, and ethyl acetate.

[0101] In the solvent dehydration process, water gas is forced through the pores by applying a vacuum from the permeate side of the membrane. Because the solvent molecules are larger than or close to the largest pores for molecular sieving (>0.55 nm) and water is very small, only water passes through. Furthermore, water is preferentially adsorbed into the hydrophilic pores in the AD region of the pores blocking the passage of other less hydrophilic molecules. Bipolar aprotic solvents are used in organic synthesis and dissolving polymers, where very small or trace amounts of water can be harmful.

[0102] Another application is the use of the supported CMSM defined above as a catalytic membrane reactor. The supported CMSM of the present invention has high potential in the field of catalytic membrane reactors, especially for the reaction of CO2 with H2, since it is easier to prepare, cheaper and has better permeation properties than the currently studied zeolite membranes, and also for hydrogen production, hydrogenation chemical reactions, dehydrogenation chemical reactions or esterification reactions in which water is produced.

[0103] The supported CMSM of the present invention can be used in process intensification for in-situ removal of water during catalytic reactions in the chemical, petrochemical, food and cosmetic sectors. In particular, in the production processes of methane, methanol, dimethyl ether, dimethyl carbonate (DMC) or other organic solvents, where water is produced in the reaction. Examples of processes in which the supported CMSM of the present invention can be used as a catalytic membrane reactor are the reaction of CO2 with H2 to produce CH4; the synthesis of esters by the reaction of alcohols with carboxylic acids; biodiesel and biolubricants; methanol produced from CO2 and H2; dimethyl ether obtained by methanol dehydration or by direct synthesis from CO2 and H2; and the synthesis of dimethyl carbonate from CO2 and methanol. By using the supported CMSM of the present invention, water is removed from the reaction products and compounds of interest, such as oxygenated solvents and esters, are produced.

[0104] Finally, the supported CMSM of the present invention can be used in the process of dehydrogenation of methylcyclohexane.

[0105] Throughout the specification and claims, the word "comprise" and variations of this word are not intended to exclude other technical features, additives, ingredients or steps.

[0106] Furthermore, the word "comprise" encompasses the case of "consisting of." Additional objects, advantages, and features of the present invention will become apparent to those skilled in the art upon examination of this description or may be learned by practice of the present invention. The following examples and drawings are provided by way of illustration and are not intended to limit the present invention. Reference signs placed within parentheses in connection with the drawings and in the claims are merely intended to enhance the clarity of the claims and should not be construed as limiting the scope of the claims. Furthermore, the present invention covers all possible combinations of the specific preferred embodiments described herein. EXAMPLES

[0107] material and method

[0108] Formaldehyde (37% VWR chemicals), N-methyl-2-pyrrolidone (NMP, 99.5%), aluminum acetylacetonate (>98%) and phenol (>99%) from Sigma-Merck and oxalic acid (98%) from Acros organics were used without further purification. Asymmetric tubular porous alumina with an outer diameter (OD) of 10 mm and an inner diameter (ID) of 7 mm, with an outer layer of alumina with a pore size of 100 nm and a length of 50 cm, supplied by Inopore Gmbh., was used as the support after being cut to a length of 15 cm. The porous support was connected on one side to a dense alumina tube and on the other side the support was closed via a glass seal which required heating of the support up to 900° C. with a heating gradient of 1.5° C. / min, a dwell time of 10 minutes and a cooling rate of 3° C. / min.

[0109] Example 1: Novolac Precursor Synthesis

[0110] 65 g of phenol was placed in a three-necked round-bottom flask equipped with a reflux condenser and heated to 50 °C for 60 min, then 1 g of oxalic acid was added while mixing with a magnetic stirrer at 500 rpm for 30 min; the temperature was increased to 85 °C and 46 g of formaldehyde was added dropwise in a period of 60 min. After 10 h of reaction, the solution was centrifuged three times at 4400 rpm and 10 °C to separate water and unreacted reactants. In the last step, the precursor was dried under vacuum at 50 °C and 4 mbar for 24 h. The obtained novolac powder was used as carbon precursor in the synthesis of CMSM.

[0111] Example 2: Preparation of the immersion solution

[0112] 20 g of the prepared novolac was mixed with 78 g of NMP in a high shear mixer (Thinky ARE-310) at 2000 rpm for 30 minutes; then the equipment was left for 10 minutes to prevent the solution from overheating; this cycle was repeated three times. Next, 1.6 g of formaldehyde was introduced into the solution and mixed at 2000 rpm for 30 minutes. Then, 0.4 g of oxalic acid was added and mixed at 2000 rpm for another 30 minutes. This mixture was used to prepare immersion solutions with various contents of Al(acac)3.

[0113] [Table 1]

[0114] Example 3: Preparation of supported CMSM. Dip coating, drying and carbonization

[0115] The prepared porous alumina support was immersed in the immersion solutions listed in Table 1 for 30 seconds at room temperature using a custom-made dip-coating machine and withdrawn at a speed of 5 mm / s. This immersion cycle was repeated five times with an interval of 20 seconds between cycles. The membrane was then immediately transferred to a rotary dryer oven and the coated support was dried at 140°C for 6 hours under argon atmosphere. The tube was then carbonized in a tubular oven (Nabertherm R 170 / 1000 / 12) with a heating gradient of 1°C / min to 500°C and the temperature was maintained for 3 hours in a flowing argon atmosphere (100 l / h). After carbonization, the CMSM was stored in a humidified chamber at 100% relative humidity (RH) to stabilize the hydrophilic sites in the CMSM for one month.

[0116] Example 4: Preparation of unsupported membrane

[0117] Unsupported membranes were prepared by pouring the immersion solution into a Teflon dish and then heating in an oven at 80° C. for 24 hours; the formed film was carbonized using the same conditions as the supported membranes.

[0118] Example 5: Physicochemical characterization.

[0119] The thickness of the films was measured using a scanning electron microscopy (SEM) Quanta 200 FEG-3D equipped with EDX (Phenom, ProX) applying a potential of 10 kV. Prior to the analysis, the samples were sputtered (Quorum, Q150RS) with Au for 30 s and 40 mA current. The reported thickness is the average of at least four measurements in different parts of the film. SEM images of CMSM obtained with an immersion solution without Al(acac)3 (M0) and with an immersion solution containing 0.7 wt% Al(acac)3 (M0.7) are shown in Figure 2.

[0120] It can be observed that a continuous layer of carbon with a thickness of about 1.5 μm, free of defects, is deposited on the porous alumina support. It was observed by SEM that the thickness of the film increases with the concentration of Al(acac)3 in the immersion solution (about 2 μm for M0.7), as shown in Figure 3. To explain this behavior, the viscosity of the immersion solution was also measured and the results are also plotted in the same figure.

[0121] The viscosity of the dipping solution was measured at 20° C. using a Brookfield, Ametek DV2T viscometer.

[0122] X-ray diffraction (XRD) analysis was performed on support-free carbon films with varying Al(acac)3 loadings in the 2θ range of 10-120°. A Niβ-filtered Cu-Kα radiator at 40 kV, 30 mA and 0.05° / min scan step was used on a Rigaku MiniFlex 600 machine. The JCPDS database was used to analyze and identify existing peaks in the spectra.

[0123] It is found that the thickness of the CMSM increases with the viscosity of the immersion solution according to the Landau-Levich equation (Eq. 1). (Formula 1) TIFF2025507358000002.tif24133

[0124] where h0, ρ, g, U0, η and γ are the thickness of the wet film, the solution density, the gravitational constant, the withdrawal rate of the ceramic support from the immersion solution, the viscosity and the surface tension of the immersion solution, respectively. C is related to the curvature of the dynamic meniscus and can be calculated experimentally.

[0125] Figure 3 shows the effect of Al(acac)3 concentration in the immersion solution on the viscosity of the solution and the thickness of the CMSM. From M0 to M2, the increase in viscosity is small, and with higher Al(acac)3, the viscosity increases sharply, which can be attributed to the formation of a complex between the OH-groups of the phenolic resin and Al(III), which behaves as a metal-chelating crosslinker. This complex formation and the increase in the viscosity of the immersion solution hinders the migration of Al(III) and avoids the formation of polyaluminum compounds such as alumina (Al2O3) and boehmite (γ-AlO(OH)).

[0126] This is shown in Figure 4 and can also be seen in the XRD spectrum of the sample where no γ-AlO / boehmite (γ-AlO(OH)) peaks were observed.

[0127] SEM-EDX analysis of M2 reveals that Al, C and O are well distributed in the film (Figure 11).

[0128] The composition of the membrane was performed using an unsupported membrane. Because the CMSM layer is very thin, both supported and unsupported CMSM membranes have very similar compositions as long as they are prepared under the same conditions.

[0129] C, H and O were determined using a Thermo Scientific Flash smart-CHNS / O analyzer.

[0130] The Al content was obtained by calcining the films at 600 °C for 3 h under air in a box oven (Nabertherm N 500 / 85 HA), dissolving the ashes at 50 °C for 24 h in concentrated nitric acid (67 wt%), then diluting the samples with 5 wt% nitric acid and determining the Al content using microwave plasma atomic emission spectroscopy (MP-AES) (Agilent, 4210).

[0131] The C, H and O elemental compositions of the films obtained by organic elemental analysis and SEM-EDX, as well as the Al composition determined by MP-AES, are listed in Table 2.

[0132] [Table 2]

[0133] The C and O compositions obtained by SEM-EDX are comparable. As expected, the amount of oxygen in the samples increases with increasing Al content; a similar trend is observed for H, suggesting that the increase is caused by the presence of OH in the films. The presence of Al2O3 is discarded due to the increase in hydrogen content and the absence of related peaks in XRD (Figure 4). The Al could be in the form of aluminum hydroxide (AlO(OH) and / or Al(OH)3) bound to the carbon matrix. As both compounds are hydrophilic, the hydrophilicity of the films should increase with the Al content in the films.

[0134] A water adsorption test was used to investigate the change in hydrophilicity within the pores of CMSM, where a CMSM sample without support was weighed and left at 100% RH for one week in a custom-built climatic chamber, after one week the sample was left at 20 °C and 30% RH for 24 h to remove the bulk water on the surface of the sample in the climatic chamber (Memmert HCP 50). The sample was then weighed again and the weight gain percentage was normalized compared to a sample without Al(acac)3 in the immersion solution.

[0135] The increase in hydrophilicity with increasing Al content in the film can be seen in Figure 5, where the weight after hydration and the ratio to the dry sample are plotted as a function of the weight (%) of Al present in the film, and the relationship is approximately linear.

[0136] Example 6: Transmission Characterization

[0137] Single gas permeation tests were performed with the permeation setup shown in Figure 1. The setup has three main parts: a) gas supply with multiple mass flow controllers (MfC); b) tubular oven with three thermocouples placed along the membrane; c) back pressure regulator, safety valve and bubble flow meter (Horiba SEC VP1 and VP3). Prior to the permeation measurements, the CMSM was kept in N2 atmosphere at 45 °C and 1 bar pressure difference (between permeate and retentate streams) for 24 h for stabilization. Single gas permeation measurements of H2 and N2 were performed at various pressure differences and temperatures. The ideal H2 / N2 selectivity (permselectivity) is the ratio of H2 and N2 flow rates at a given temperature and pressure. The CMSM with the best performance in terms of H2 / N2 permselectivity was tested for 720 h; at 150 °C and 6 bar pressure difference; H2 and N2 fluxes were measured daily.

[0138] Example 7: Determination of pore size distribution using perm porosimetry

[0139] This method uses capillary condensation as a tool to block pores via adsorption of water molecules within the pores of CMSM at the specific humidity level to which the membrane is exposed. In pores smaller than 2 nm, confinement and condensation below the saturation vapor pressure increases the interactions of the adsorbed molecules with each other and with the walls of the nanopores. The relationship between the relative vapor saturation pressure and the pore size of CMSM is described by the Kelvin equation (Eq. S1): (Formula S1) TIFF2025507358000004.tif24133

[0140] In the formula, r p , V m ,σ,θ,P,Ps , R and T are the pore radius, molar volume of the condensed liquid, condensation surface tension, contact angle of the liquid with the wall of the CMSM, partial pressure of the condensable vapor, saturation pressure of the condensable vapor, gas constant and temperature, respectively.

[0141] The setup consists of a gas supply, a water injection system, a catalytic membrane reactor, a flow meter and a condenser. Figure 1B shows a schematic diagram of the perporometry setup.

[0142] Prior to the perm porosimetry test, the CMSM was heated at 400°C for 48 hours in N2 atmosphere to remove water molecules from the pores. The pressure, temperature and N2 feed flow rate in the MFC were set, and the N2 flow rate in the permeate of the CMSM was measured with a bubble flow meter (Horiba SEC, VP1, VP2). After membrane stabilization (60 min), a water flow was injected using an HPLC pump; after 30 min of equilibration, the N2 permeate flow rate was measured. The flow was measured every 30 min until the difference with the previous measurement fluctuated by less than 5%. Then, more water was injected according to the described protocol until no N2 permeation was detected. Finally, the pore size distribution was calculated according to the decrease in the flow rate in the permeate at each step of condensable vapor injection.

[0143] Example 8: Palm Porosimetry Test

[0144] Measurements of the active pore size in CMSM were performed using a custom-built (Figure 1B) capillary condensation perm porosimeter.

[0145] The effect of aluminum hydroxide on the pore size of CMSM was analyzed by perm porosimetry.

[0146] In this method, as the ratio of water vapor to non-condensable gas (N2) increases, the condensation of water in the pores gradually blocks the passage of other gases from the smallest to the largest pores. Since the kinetic diameter of N2 is 0.364 nm, this method can only measure pores larger than around 0.4 nm.

[0147] The effect of Al(acac)3 on the pore size distribution of CMSM calculated by porosimetry is shown in Figure 6 and in the table below.

[0148] [Table 3]

[0149] The CMSM without Al(acac)3, M0, has the largest pores; the higher percentage of pores is around 0.72 nm, other larger ones are present up to 1.2 nm, where no more pores are observed.

[0150] With the introduction of Al(acac)3, the smallest pore detected shifted to smaller pores (0.6, 0.55 and 0.49 nm for M0.7, M2 and M4, respectively). Only one pick is observed in M4, showing a very narrow pore size distribution (66% of the pores are smaller than 0.5 nm).

[0151] The predominance of the smallest pores in the membranes exhibits a volcano shape upon the addition of Al(acac)3 and is maximum for M4.

[0152] Example 9: CMSM Permeation Test

[0153] For the qualitative analysis of the presence of defects in the membrane, pores larger than 50 nm could be considered as defects. The N2 permeance of CMSM can be attributed to the contributions of Knudsen (pores 2-50 nm) and viscous flow (pores >50 nm) transport mechanisms; the flux in micropores (<2 nm) is low and therefore the contribution can be neglected. Thus, the observed permeance (Perm obs ) is a member of the Knudsen (Perm Kundsen ) and viscous flow (Perm viscous ) contribution (Eq. 2) Permeance obs = Permeance Knudsen +Permeance viscous =α+βP (Equation 2)

[0154] When the observed permeability is plotted against the pressure difference (P), a positive gradient (β) indicates the presence of defects (>50 nm). Figure 7 plots the results of the N2 permeability of CMSM against the applied pressure difference between the holding liquid and the permeate liquid.

[0155] As can be seen in Figure 7, the gradient of the membrane can be considered zero, which reveals that the membrane does not contain defects. The maximum and minimum permeabilities correspond to M0 and M4, respectively, and are consistent with the pore size distribution shown in Figure 6 where M0 has the largest pores and M4 is the smallest.

[0156] The permeation characteristics of the membrane for hydrogen separation are the hydrogen permeability and the H2 / N2 ideal selectivity at a given temperature and pressure. Figures 12 and 13 show the H2 and N2 permeabilities of CMSM as a function of the permeation temperature and the content of Al(acac)3 in the immersion solution. Since the thickness of CMSM depends on the viscosity of the immersion solution, the permeabilities (permeabilities) normalized by the thickness are shown in Figures 14 and 15. Figure 8 shows the H2 / N2 ideal selectivity of CMSM at a pressure difference of 6 bar as a function of the permeation temperature for various Al(acac)3 contents. M4 has the highest selectivity at all temperatures; generally, the H2 / N2 ideal selectivity at a given temperature follows the order M0 < M0.7 < M2 < M6 < M4, which is related to the volcano shape for the minimum pore size distribution (Figure 6) and the N2 permeability (Figure 7).

[0157] As shown in Figure 8, the effects of temperature and added Al(acac)3 on the H2 / N2 selectivity. M4 shows the highest ideal selectivity at all temperatures compared to other CMSMs within the test range. According to the H2 and N2 permeabilities (Figures 12 and 13), above 300 °C, the sharp increase in gas permeation is an indicator of unstable CMSM performance. The unstable performance is observed due to changes in the carbon matrix and, as a result, changes in the pore size and pore size distribution, leading to a sharp decrease in the H2 / N2 ideal selectivity (Figure 8).

[0158] The H2 / N2 permeation performance of the CMSMs in this study is compared with polymeric membranes and other carbon membranes from the literature by introducing H2 permeability and H2 / N2 ideal selectivity into the Robeson plot (Figure 9). All the CMSMs of the present invention tested are well above the Robeson upper limit. In addition to polymer membranes, the performance of the CMSM of the present invention was also evaluated by comparing the performance of the CMSM with that of phenolic resin (PR) (see M. Texeira et al., “Boehmite-phenolic resin carbon molecular sieve membranes-Permeation and adsorption studies” Chem. Eng. Res. Des. 2014, vol. 92, no. 11, pp. 2668-2680) or PR / PAA (see L. Li, C. Song, H. Jiang, J. Qiu, and T. Wang, “Preparation and gas separation performance of supported carbon membranes with ordered mesoporous carbon interlayer,” J. Memb. Sci., vol. 450, pp. 469-477, Jan. 2014) and PDMS (A.K. Itta, H.T. Sheng, and M.Y. Wey, “Fabrication and characterization of PPO / PVP blend carbon molecular sieve membranes for H2 / N2and The performance of CMSMs is compared to that of CMSMs found in the literature prepared using different precursors such as Al(acac)3 (see “H2 / CH4 separation,” J. Memb. Sci., vol. 372, no. 1-2, pp. 387-395, Apr. 2011). The performance of CMSMs improves as the Al(acac)3 content increases, reaching a maximum value for the M4 membrane, exceeding the reported values ​​for CMSMs in the literature.

[0159] The long-term stability of M4 was tested by analyzing H2 permeance and H2 / N2 ideal selectivity at 150°C and 6 bar pressure difference for 720 hours. Figure 10 shows that M4 was stable throughout the test with a maximum 5.7% SD variation in H2 / N2 ideal gas selectivity and 7.04% SD variation in H2 permeance.

[0160] In summary, elemental analysis shows that O and H content in CMSM increases with Al content, suggesting the presence of hydrophilic aluminum compounds containing hydrophilic groups, which was demonstrated by water adsorption studies. The formation of complexes of Al with OH of phenolic groups affects the pore size distribution of the membranes; M0 (without Al) has the largest pores, and the pores became smaller with the addition of Al(acac)3. M4 has the smallest pore size distribution with a sharp pore size distribution, which is reflected in the permeation properties of this membrane, and has the highest H2 / N2 selectivity in permeation in the temperature range of 50-350 °C. All prepared membranes are well above the upper binding limit of the polymer membrane. The M4 membrane was stable to H2 permeation for 720 h at 150 °C and 6 bar ΔP.

[0161] Terms

[0162] Clause 1. A supported carbon molecular sieve membrane having aluminum atomically distributed therein, the aluminum being present in an amount of 15% by weight or less of the carbon molecular sieve membrane; the membrane comprising a pore size distribution in which at least 70% of the pores have a pore size of 0.25 to 0.7 nm; the supported carbon molecular sieve membrane being obtainable by dip coating the support with a solution comprising a phenolic resin and aluminum ions, followed by carbonization.

[0163] Clause 2. The supported carbon molecular sieve membrane of clause 1, wherein the membrane comprises a pore size distribution in which at least 60% of the pores have a pore size between 0.25 and 0.6 nm.

[0164] Clause 3. The supported carbon molecular sieve membrane of any of clauses 1-2, wherein at least 85% of the pores have a pore size of 0.25 to 0.6 nm.

[0165] Clause 4. The supported carbon molecular sieve membrane of any one of clauses 1 to 3, wherein the support of the carbon molecular sieve membrane is a porous alumina support.

[0166] Clause 5. The supported carbon molecular sieve membrane of any one of clauses 1 to 4, wherein the phenol formaldehyde resin is a synthetic phenol formaldehyde resin.

[0167] Clause 6. The supported carbon molecular sieve membrane of any one of clauses 1 to 5, wherein the aluminum ions are in the form of aluminum acetylacetonate.

[0168] Clause 7. The supported carbon molecular sieve membrane of any of clauses 1-6, wherein the aluminum is present in an amount of 1% to 11% by weight of the carbon molecular sieve membrane.

[0169] Clause 8. The supported carbon molecular sieve membrane of clause 7, wherein the aluminum is present in an amount of 7% to 9% by weight of the carbon molecular sieve.

[0170] Clause 9. The supported carbon molecular sieve membrane of any one of clauses 7 to 8, wherein the carbon content is from 75% to 95% by weight, the oxygen content is from 2.5% to 8% by weight, and the hydrogen content is from 1.5% to 6% by weight.

[0171] Clause 10.a) providing a porous support; b) providing a coating solution comprising a phenol formaldehyde resin as a carbon precursor, a non-aqueous solvent, formaldehyde, an acid, and aluminum ions in the form of a suitable salt or complex as a metal precursor; c) immersing the porous alumina support in the solution of step b) at least once; d) optionally drying the coated aluminum support of step c); e) heating the dried support of step d) to a final pyrolysis temperature and non-oxidizing atmosphere sufficient to form a supported carbon sieve membrane containing aluminum; and f) cooling the supported carbon sieve membrane of step e) to room temperature; Including, 10. A process for preparing a supported carbon molecular sieve membrane according to any one of clauses 1 to 9.

[0172] Clause 11. The process of clause 10, wherein the pyrolysis temperature is between 350°C and 1100°C and is carried out in a non-oxidizing atmosphere or under vacuum.

[0173] Clause 12. A process for separating a gas molecule, which is H2, from a gas mixture of the gas molecule and at least one other gas molecule, comprising: a) providing a supported carbon molecular sieve membrane according to any one of clauses 1 to 9; b) providing a gas mixture comprising at least two gases; and c) feeding the gas mixture to a supported carbon molecular sieve membrane at a temperature of from -80°C to 300°C to obtain a retentate stream having a reduced concentration of gas molecules and a permeate stream having an increased concentration of gas molecules.

[0174] Clause 13. The process of clause 12, wherein the gas mixture comprising at least two gases is selected from the group consisting of H2 / CH4; H2 / N2; H2 / CO2.

[0175] Clause 14. Use of a supported CMSM according to any of clauses 1 to 9 for H2 recovery from a natural gas grid, H2 production from biomass, solvent dehydration, obtaining oxygen-enriched air, or dehydrogenation of methylcyclohexane.

[0176] Clause 15. Use of a supported CMSM according to any of clauses 1 to 9 as or as part of a catalytic membrane reactor.

Claims

1. A supported carbon molecular sieve membrane having aluminum atomically distributed therein, wherein the aluminum is incorporated into the carbon molecular sieve membrane in the form of a single atom; the aluminum is present in an amount of 15% or less by weight of the carbon molecular sieve membrane; the membrane comprises a pore size distribution in which at least 70% of the pores have a pore size between 0.25 and 0.7 nm as measured by perm porosimetry; The carbon molecular sieve membrane has a carbon content of 75% to 95% by weight, an oxygen content of 2.5% to 8% by weight, and a hydrogen content of 1.5% to 6% by weight; and A supported carbon molecular sieve membrane obtainable by dip-coating a support with a solution containing phenol formaldehyde resin and aluminum ions in the form of a suitable salt or complex as a metal precursor, followed by carbonization, said suitable salt or complex having an organic anion or an organic neutral ligand.

2. 10. The supported carbon molecular sieve membrane of claim 1, wherein the membrane comprises a pore size distribution in which at least 60% of the pores have a pore size between 0.25 and 0.6 nm.

3. 3. The supported carbon molecular sieve membrane of claim 1, wherein at least 85% of the pores have a pore size of from 0.25 to 0.6 nm.

4. 4. The supported carbon molecular sieve membrane of claim 1, wherein the support of the carbon molecular sieve membrane is a porous alumina support.

5. 5. The supported carbon molecular sieve membrane of claim 1, wherein the phenol formaldehyde resin is a synthetic phenol formaldehyde resin.

6. 6. The supported carbon molecular sieve membrane of claim 1, wherein the aluminum ions are in the form of aluminum acetylacetonate.

7. 7. The supported carbon molecular sieve membrane of claim 1, wherein the aluminum is present in an amount of from 1% to 11% by weight of the carbon molecular sieve membrane.

8. 8. The supported carbon molecular sieve membrane of claim 7 wherein said aluminum is present in an amount of from 1% to 9% by weight of said carbon molecular sieve membrane.

9. 9. The supported carbon molecular sieve membrane of claim 8 wherein said aluminum is present in an amount of from 7% to 9% by weight of said carbon molecular sieve.

10. a) providing a porous support; b) providing a coating solution comprising a phenol formaldehyde resin as a carbon precursor, a non-aqueous solvent, formaldehyde, an acid, and aluminum ions in the form of a suitable salt or complex as a metal precursor; c) immersing the porous alumina support in the solution of step b) at least once; d) optionally drying the coated aluminum support of step c); e) heating the dried support of step d) to a final pyrolysis temperature and non-oxidizing atmosphere sufficient to form said supported carbon sieve membrane containing aluminum; f) cooling the supported carbon sieve membrane of step e) to room temperature; Including, The suitable salt or complex has an organic anion or an organic neutral ligand, A process for preparing the supported carbon molecular sieve membrane according to any one of claims 1 to 9.

11. 11. The process of claim 10, wherein the pyrolysis temperature is from 350° C. to 1100° C. and is carried out in a non-oxidizing atmosphere or under vacuum.

12. A gas mixture of the gas molecule and at least one other gas molecule. 2 1. A process for separating gas molecules which comprises: a) providing a supported carbon molecular sieve membrane according to any one of claims 1 to 9; b) providing a gas mixture comprising at least two gases; c) feeding the gas mixture to the supported carbon molecular sieve membrane at a temperature of from −80° C. to 300° C. to obtain a retentate stream having a reduced concentration of the gas molecules and a permeate stream having an increased concentration of the gas molecules.

13. The gas mixture containing at least two gases is H 2 / CH 4 ;H 2 / N 2 ;H 2 / CO 2 The process of claim 12, wherein the compound is selected from the group consisting of:

14. H from the natural gas grid 2 Recovery, H from biomass 2 10. Use of the supported CMSM according to any one of claims 1 to 9 for the production, solvent dehydration, obtaining oxygen-enriched air, or dehydrogenation of methylcyclohexane.

15. 10. Use of a supported CMSM according to any one of claims 1 to 9 as a catalytic membrane reactor or as part of a catalytic membrane reactor.

Citation Information

Patent Citations

  • Metallopolyimide precursor fibers for aging-resistant carbon molecular sieve hollow fiber membranes with enhanced selectivity

    US10112149B2

  • Carbon molecular sieve membranes containing a group 13 metal and method to make them

    WO2019089087A1

  • Carbon molecular sieve membrane and its use in separation processes

    WO2021116319A1